USEFUL TIPS IN WRITING SKILLS IMPROVEMENT FOR HIGH SCHOOL LEARNERS - Jurakulova , Durdona; Yugay , Yevgeniya (Innovative Development in Educational Activities, 2023)
Improving the writing skills of high school learners is a multifaceted endeavor that encompasses various aspects of language, communication, and critical thinking. This thesis aims to explore and provide comprehensive guidance on enhancing the writing skills of high school students through a combination of pedagogical strategies, digital tools, and a supportive learning environment.